Notes on the Modal Predicator naada in Sakha (from a Taimyr Dolgan Perspective) - Florian Siegl (Studia Orientalia Electronica, 2021)
This paper addresses the syntax, semantics, and history of the modal deontic predictors naada and tustaax in Sakha and contrasts their use with Sakha's closest linguistic relative Taimyr Dolgan. In this respect, this study is a continuation of Siegl (2019), which, in passing, already reported similarities and dissimilarities in these two closely related Turkic languages of Northern and Northeastern Siberia. A contrastive analysis based on recent translations of the Gospel of Luke (which for the time being is the only longer text available in both languages) confirms that the genealogical proximity of Sakha and Taimyr Dolgan is not reflected in the use of naada and tustaax. The study concludes with a superficial look at the fate of Russian nado in Kolyma and Tundra Yukaghir. Even though the lexeme is obviously of Russian origin, Kolyma Yukaghir but especially Tundra Yukaghir data shows several similarities with Sakha naada, which are absent from Russian and therefore imply Sakha influence.